The Removal of Iron Oxide From Kaolin Clay by Hydrometallurgy Method - Jassam Mohammad, Mahasin (Anbar Journal of Engineering Science, 2011)
The research deals with a study carried out on the influence of iron oxide (Fe2O3) on the characteristics of kaolin clay and the possibility of reducing iron oxide percentage in kaolin clay in the location of Ghamij in Anbar Governorate, prior to using it in industry. The raw material used in the research contained about 5.72% of iron oxide. When such a percentage of iron oxide is contained in kaolin clay, it makes it harmful in numerous industries such as paper, plastic, drugs etc….. In this research the hydro metallurgy method was used where oxalic acid was diluted with distilled water, and with the help of heat and mixing ( as assisting factor) to cause iron oxide to melt and thereafter subjected to filtration and thus the ‘Bakkag’, i.e. white kaolin which was almost free from iron oxide was obtained. The sample of kaolin raw material weighted about 25 grammas and the acid diluted in the distilled water used along periods of (2, 3) hours weighted (4,5,6,7,8,10) grammas. The findings showed that this method is very practical in ridding the kaolin samples from iron oxide; in the sample where the concentration of the acid amounted to 6 along a 3- hour period, the percentage of iron oxid reduced to 3.2% In this way much of iron oxide melted and even its red color of the raw material changed to white. The same result was obtained by using a No. 10 concentration acid was used for two hours, the percentage of iron oxid reduced to 3.18%.The construction of iron oxide reach to 45%,the loss in weight of raw material used in this research is about 14%.